The influence of chiropractic care on cervical pain of postural (Research, Society and Development, 2021)
Objective: The aim of this research is to determine the influence of chiropractic on cervical pain of postural origin in students of a Higher Education Institution. Methods: This is a field research with application of an evaluation form for data collection and application of the chiropractic technique. The application of the evaluation form consisted of topics such as: identification, special tests for cervical, followed by the application of the VAS scale at the beginning and after each session thus evaluating the patient's pain, totaling four sessions in all, lasting 20-30 minutes, and with an interval of 7 to 10 days between sessions. Results: In general, chiropractic presents significant results for the treatment of cervical pain, obtaining better efficacy mainly after the four sessions, but further studies are needed to better highlight the potential of the technique.